Judicial Artificial Intelligence Bias: A Survey and Recommendations - Ngige, Ogochukwu Constance; Awodele, Oludele; Balogun, Oluwatobi (Transactions on Engineering and Computing Sciences, 2021)
Artificial intelligence (AI) has continued to disrupt the way tasks are being carried out, finding its way into almost all facets of human existence, and advancing the development of human society. The AI revolution has made huge and significant inroad into diverse industries like health, energy, transport, retail, advertising, et cetera. AI has been found to assist in carrying out tasks more quickly and efficiently too. Tasks which were hitherto difficult have been simplified significantly through the use of AI. Slow adoption in judiciary has however been reported, compared to other sectors. A lot of factors have been attributed to this, with AI bias being an issue of concern. Decisions emanating from courts have a significant impact on an individual’s private and professional life. It is thus imperative to identify and deal with bias in any judicial AI system in order to avoid delivering a prejudiced and inaccurate decision, thereby possibly intensifying the existing disparities in the society. This paper therefore surveys judicial artificial intelligence bias, paying close attention to types and sources of AI bias in judiciary. The paper also studies the trust-worthy AI, the qualities of a trust-worthy artificial intelligence system and the expectations of users as it is being deployed to the judiciary, and concludes with recommendations in order to mitigate the AI bias in Judiciary.